2019
DOI: 10.1007/s00417-019-04569-8
|View full text |Cite
|
Sign up to set email alerts
|

Off-label use of bevacizumab for wet age-related macular degeneration in Europe

Abstract: Purpose To analyse current off-label use of bevacizumab for wet age-related macular degeneration (AMD) in Europe. Methods The study was conducted as a combined survey and literature review. It included the 22 most populous countries in Europe. In each country, ophthalmologists with particular knowledge about off-label treatment responded to a questionnaire. Results Answers were obtained from twenty European countries. The off-label use of bevacizumab for wet AMD greatly differed between nations; the bevacizuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 24 publications
0
29
0
1
Order By: Relevance
“…Bevacizumab (IVB) is a monoclonal, humanized, fulllength antibody inhibiting vascular endothelial growth factor (VEGF). Currently, bevacizumab is widely used in DME treatment as an off-label drug [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Bevacizumab (IVB) is a monoclonal, humanized, fulllength antibody inhibiting vascular endothelial growth factor (VEGF). Currently, bevacizumab is widely used in DME treatment as an off-label drug [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…While no significant drop of visual acuity was reported after the switch, 18-19% of patients were found to be non-responder to bevacizumab and switched back to ranibizumab or aflibercept [41]. Different attitudes towards the off-label use of bevacizumab in nAMD across the European Nations have been shown by a recent report [42]; indeed in Europe the use of bevacizumab in nAMD may vary considerably, ranging from non-existent (Switzerland, Hungary, Denmark) to very frequent (Romania, Bulgaria, Finland, Ireland, Netherlands). Moreover, large disparities within single countries, resulting from different organization of the National Health Systems and regional autonomies have been reported [42].…”
Section: Current Trends and Future Directionsmentioning
confidence: 98%
“…Different attitudes towards the off-label use of bevacizumab in nAMD across the European Nations have been shown by a recent report [42]; indeed in Europe the use of bevacizumab in nAMD may vary considerably, ranging from non-existent (Switzerland, Hungary, Denmark) to very frequent (Romania, Bulgaria, Finland, Ireland, Netherlands). Moreover, large disparities within single countries, resulting from different organization of the National Health Systems and regional autonomies have been reported [42]. In the United Kingdom, until recent years, the General Medical Council and the National Institute for Health and Care Excellence (NICE) guidelines have not encouraged ophthalmologists to use bevacizumab in nAMD [43].…”
Section: Current Trends and Future Directionsmentioning
confidence: 99%
“…Although multiple studies have confirmed the comparable efficacy and safety of intravitreal bevacizumab (Avastin ® ) administration to registered anti-VEGF drugs (4)(5)(6)(7)(8)(9), bevacizumab continues to have an off-label status. A recent study evaluating bevacizumab use in 20 European countries showed that a consensus on the ophthalmic off-label use of bevacizumab in Europe has not yet been reached and member states have different approaches (10). Bevacizumab intravitreal injections quota significantly varies in different European countries and even developed economies use bevacizumab after informed consent is obtained.…”
Section: Influence Of Unilateral Intravitreal Bevacizumab Injection Omentioning
confidence: 99%